Distinct Elements Confer the Blocking and Bypass Functions of the Bithorax Fab-8 Boundary. Issue 3 (1st November 2019) - Kyrchanova, Olga; Wolle, Daniel; Sabirov, Marat; Kurbidaeva, Amina; Aoki, Tsutomu; Maksimenko, Oksana; Kyrchanova, Maria; Georgiev, Pavel; Schedl, Paul
Abstract: Boundaries in the Drosophila bithorax complex (BX-C) enable the regulatory domains that drive parasegment-specific expression of the three Hox genes to function autonomously. The four regulatory domains ( iab-5, iab-6, iab-7, and iab-8 ) that control the expression of the Abdominal-B ( Abd-B ) gene are located downstream of the transcription unit, and are delimited by the Mcp, Fab-6, Fab-7, and Fab-8 boundaries. These boundaries function to block cross talk between neighboring regulatory domains. In addition, three of the boundaries ( Fab-6, Fab-7, and Fab-8 ) must also have bypass activity so that regulatory domains distal to the boundaries can contact the Abd-B promoter. In the studies reported here, we have undertaken a functional dissection of the Fab-8 boundary using a boundary-replacement strategy. Our studies indicate that the Fab-8 boundary has two separable subelements. The distal subelement blocks cross talk, but cannot support bypass. The proximal subelement has only minimal blocking activity but is able to mediate bypass. A large multiprotein complex, the LBC (large boundary complex), binds to sequences in the proximal subelement and contributes to its bypass activity. The same LBC complex has been implicated in the bypass activity of the Fab-7 boundary.